Later lines in pMMR/MSS metastatic colorectal cancer: News opportunities with immunotherapy and local treatments - Alfredo Colombo; Concetta Maria Porretto (Society of Gastrointestinal Intervention, 2024)
Colorectal cancer (CRC) is one of the most prevalent malignancies, and most patients are diagnosed with metastatic disease at first presentation. However, immunotherapy is particularly useful only in a limited number of patients with mismatch repair-deficient/high microsatellite instability metastatic CRC (mCRC), while most patients have proficient mismatch repair (pMMR)/microsatellite stability (MSS). Currently, many clinical research on immunotherapy in association with tyrosine kinase inhibitors are aiming to modulate the immune microenvironment of pMMR/MSS mCRC and turn "cold tumors" into "hot tumors," which has not only unanticipated implications, but also good results. Some consequences include that the response may not be selective for metastases. This review summarizes recent studies on potential mechanisms of immunotherapy combined with local therapy (including radiotherapy, ablation, and transcatheter arterial chemoembolization) in the treatment of metastases.